The potential of exercise to reverse stress induced abnormalities in the rat brain - Marais, Lelanie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biomedical Sciences. Medical Physiology.))--University of Stellenbosch, 2010.